TATA REHABILITASI PENYALAHGUNAAN NARKOBA DI KABUPATEN BANYUWANGI DALAM PERSPEKTIF PERATURAN DAERAH 7/2020 - Sieta Rizky Dwi Cahyanti; Hary Priyanto; Leni Vitasari (Nusantara Hasana Journal, 2023)
Background: Drug abuse in Banyuwangi Regency is the result of people's lack of understanding of the dangers posed. Causes of drug abuse from internal and external factors. It is important that the Government of Banyuwangi Regency facilitates efforts to prevent and eradicate drug abuse, illicit traffic, and drug precursors. Objective: To describe, analyze, and interpret rehabilitation governance in dealing with drug abuse in Banyuwangi Regency. Method: Using qualitative principles according to constructive and participatory models. Primary data from interviews, and secondary data from the results of literature studies and various regulations relevant to the substance of the research. Results: The program for managing drug abuse handlers based on planning, organizing, directing, and monitoring has proven effective in handling narcotics abuse in Banyuwangi Regency. Conclusion: Development of medical rehabilitation institutions, as well as involving the participation of all parties in implementation and supervision is important.